Shape-tailorable high-energy asymmetric micro-supercapacitors based on plasma reduced and nitrogen-doped graphene oxide and MoO2 nanoparticles. Issue 23 (31st May 2019) - Zhang, Liangzhu; Chen, Zhiqiang; Zheng, Shuanghao; Qin, Si; Wang, Jiemin; Chen, Cheng; Liu, Dan; Wang, Lifeng; Yang, Guoliang; Su, Yuyu; Wu, Zhong-Shuai; Bao, Xinhe; et al.
Abstract : High-energy asymmetric micro-supercapacitors have been fabricated with diversified planar geometries. Abstract : Asymmetric micro-supercapacitors (AMSCs) are considered to be highly competitive miniaturized energy-storage units for wearable and portable electronics. However, the energy density, voltage output and fabrication technology for AMSCs remain challenges for practical applications. Herein, we adopt plasma reduced and nitrogen-doped graphene oxide with a high nitrogen content of 8.05% and ultra-fine MoO2 nanoparticles with a diameter of 5–10 nm as electrode materials for high-energy flexible all-solid-state AMSCs. The AMSCs based on plasma reduced and nitrogen-doped graphene oxide (PNG) and plasma reduced and nitrogen-doped graphene oxide–MoO2 composite films (PNG–MoO2 ) can be integrated on diverse substrates ( e.g., cloth, glass, leaves, and polyethylene terephthalate (PET) films) and tailored into microelectrodes with various planar geometries by accurate laser cutting. The resulting PNG//PNG–MoO2 -AMSCs exhibit a high working voltage of 1.4 V, a significant areal capacitance of 33.6 mF cm −2 and an outstanding volumetric capacitance of 152.9 F cm −3 at 5 mV s −1, and offer an exceptionally high energy density of 38.1 mW h cm −3, outperforming most reported AMSCs. Furthermore, the microdevices demonstrate electrochemical performance with excellent stability under various bending conditions up to 180° and without obvious capacitance degradation even after being bent at 60° for 1000 times. Furthermore, PNG//PNG–MoO2 -AMSCs displayed exceptional serial and parallel integration to boost the output of voltage and capacitance. This work demonstrates the great potential of such AMSCs for practical application in miniaturized, wearable, and flexible electronics.